PENINGKATAN HASIL BELAJAR AKHLAK MATERI HORMAT KEPADA GURU DAN ORANG TUA MELALUI METODE ROLE PLAYING PADA SANTRI TPQ TA'ARROFUL MUSLIMIN - Habibullah; Fatin Faruq Fadhlillah; Moh. Adam Rasuli; Devy Habibi Muhammad (Al Arsy: Journal of Education, Management and Islamic Thought, 2026)
In the learning process of Akhlak (Islamic moral education), teachers are required to select appropriate teaching methods that align with the learning objectives, student characteristics, and instructional materials. The use of suitable methods is expected to improve students’ understanding and facilitate the implementation of moral values in their daily lives. This study aimed to investigate the implementation of the role-playing method in improving learning outcomes on the topic of respecting teachers and parents at TPQ Ta'arroful Muslimin, Mangunharjo Village, Mayangan District, Probolinggo City. This study employed Classroom Action Research (CAR) conducted in two cycles involving 15 students. The research instruments included learning achievement tests, observation sheets, and documentation. The results indicated that the implementation of the role-playing method successfully improved students’ learning outcomes in each cycle. In the pre-cycle stage, the learning mastery percentage was 26.67%, which increased to 40.00% in Cycle I and reached 80.00% in Cycle II. Furthermore, the role-playing method enhanced students’ participation and engagement throughout the learning process. Therefore, it can be concluded that the role-playing method is effective in improving learning outcomes in Akhlak, particularly on the topic of respecting teachers and parents, at TPQ Ta'arroful Muslimin, Mangunharjo Village, Mayangan District, Probolinggo City.